Short sleep—poor sleep? A polysomnographic study in a large population‐based sample of women. (4th January 2019) - Åkerstedt, Torbjörn; Schwarz, Johanna; Gruber, Georg; Theorell‐Haglöw, Jenny; Lindberg, Eva
Abstract: There is a lack of studies on the association between total sleep time (TST) and other polysomnographical parameters. A key question is whether a short sleep is an expression of habitual short sleep, or whether it reflects temporary impairment. The purpose of the present study was to investigate the association between TST and amount of sleep stages and sleep continuity measures, in a large population‐based sample of women ( n  = 385), sleeping at home in a normal daily life setting. The results show that sleep efficiency, N1 (min), N2 (min), REM (min), REM% and proportion of long sleep segments, increased with increasing TST, whereas the number of awakenings/hr, the number of arousals/hr, N1% and REM intensity decreased. In addition, longer sleep was more associated with TST being perceived as of "usual" duration and with better subjective sleep quality. TST was not associated with habitual reported sleep duration. It was concluded that short TST of a recorded sleep in a real‐life context may be an indicator of poor objective sleep quality for that particular sleep episode. Because individuals clearly perceived this reduction, it appears that self‐reports of poor sleep quality often may be seen as indicators of poor sleep quality. It is also concluded that PSG‐recorded sleep duration does not reflect habitual reported sleep duration in the present real‐life context.